Three-dimensional α-Fe2O3/carbon nanotube sponges as flexible supercapacitor electrodes. Issue 42 (7th August 2015) - Cheng, Xiaoping; Gui, Xuchun; Lin, Zhiqiang; Zheng, Yongjia; Liu, Ming; Zhan, Runze; Zhu, Yuan; Tang, Zikang
Abstract : The porous, flexible and compressible CNT@Fe2 O3 sponges show high specific capacitance (>300 F g −1 ). Abstract : Flexible supercapacitors, which can sustain large deformations while maintaining normal functions and reliability, are playing an increasingly important role in portable electronic devices. Here we report the preparation of a three-dimensional α-Fe2 O3 /carbon nanotube (CNT@Fe2 O3 ) sponge electrode with a porous hierarchical structure, consisting of a compressible, conductive CNT network, coated with a layer of Fe2 O3 nanohorns. The specific capacitance of these hybrid sponges has been significantly improved to above 300 F g −1, while the equivalent series resistance remains at about 1.5 Ω. The highly deformed CNT@Fe2 O3 sponge retains more than 90% of the original specific capacitance under a compressive strain of 70% (corresponding to a volume reduction of 70%). The hybrid sponge still works stably and sustains a similar specific capacitance to the initial value even after 1000 compression cycles at a strain of 50%. The outstanding properties of this hybrid sponge make it a highly promising candidate for flexible energy devices.